115 Family experiences of flying and testing: 'fitness to fly'. (30th November 2020) - Pike, Katharine; Kelly, Paula; Brotherston, Stephanie; Riley, Mollie; Samuels, Martin
Abstract : As part of a feasibility study investigating a new protocol for hypoxic challenge testing (HCT) in children with neuromuscular weakness or central hypoventilation who use ventilation at home, we conducted interviews evaluating parents' and children's experiences of flying and this pre-flight testing. The new protocol may better advise patients who use ventilators about their 'fitness to fly'. We have recruited 15 children, 7 with neuromuscular weakness, and 8 with central hypoventilation to date (mean age 8.5 years, range 1.7 to 16.7 years), all of whom have sat in an airtight chamber with an oxygen concentration 15% (normal 21%) to simulate the in-flight environment. Patients had monitoring of oxygen saturation, end tidal and transcutaneous carbon dioxide in air, 15% oxygen, and then with supplemental oxygen, ventilation and if needed, both. Semi-structured interviews immediately after the HCT and by telephone 3–4 months later identified the following factors from the preliminary analysis of interview transcripts. Parents identified the challenges they faced when planning and undertaking air-travel, including repeated negotiations with airlines, on provision of oxygen, accommodating essential equipment thereby requiring families to be proactive managers. Despite these challenges several families were frequent travellers, who valued opportunities to visit extended family and enjoy new experiences as a whole family. During interviews older children identified travel as an opportunity for normalisation of their lives. Some families remained cautious about air travel expressing concerns about their child's underlying vulnerability. Parents and children provided valuable feedback on the experience of the HCT protocol, including challenges of space for wheelchairs and equipment in the chamber, the importance of considering school attendance in the context of multiple hospital appointments. Overall the testing process and results were seen positively by many, it built confidence for parents by providing more information about their child's responses to flight to aid future decision making.